Analysis of Regional Government Expenditure on Economic Growth of District and City in East Java - Widya Sylviana; Rosa Dewi Puspita (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
This study aims to test and assess the impact of local government expenditure on health, infrastructure, and labor on the economic growth of districts and cities in East Java Province between 2013 and 2022. This study employed the panel data regression method, using data from 38 districts and cities in East Java Province from 2013 to 2022. The study findings show that government expenditure on health, infrastructure, and labor has a favorable and considerable impact on the economic growth of East Java Province’s districts and cities.